The Effect Of Quipper School Learning Media On Students' Learning Outcomes In Grade Xi History Subjects At State High School 2 Model Palembang - Mutmainnah Mutmainnah; Hudaidah Hudaidah; Syafruddin Yusuf (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2019)
The research entitled “The Influence of Quipper School Learning Media for Studying Results at the Student’s Class XI in Historical Subjects at Islamic State Senior High School No 2 Model Palembang”. The formulation of the problem in this study, is the influence of the application of Quipper School learning media for studying results at the student’s class XI in Historical subjects at the Islamic State Senior High School No 2 Model Palembang. The purpose of this study is to determine the effect of the use of Quipper School learning media for studying results at the student’s class XI in Historical subject at the Islamic State Senior High School No 2 Model Palembang. This type of research is quasi experiment. The population in this study were all students of class XI at Islamic State Senior High School No 2 Model Palembang. The sampling technique uses random sampling, so the class XI MIA 3 is selected as the experimental class with 45 students. The statistical test used in this study is regression test. Known Fhitung 42,61 while Ftabel 4,07. Because Fhitung > Ftabel, then reject Ho and accept Ha, meaning that applying Quipper School learning media has an effect for the studying results of at the students class XI in Historical subjects at the Islamic State Senior High School No 2 Model Palembang.